If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Z = -3x + 3y + 5 Reorder the terms: Z = 5 + -3x + 3y Solving Z = 5 + -3x + 3y Solving for variable 'Z'. Move all terms containing Z to the left, all other terms to the right. Simplifying Z = 5 + -3x + 3y
| 25n^2-24n+16=0 | | 2x^2+4px+p^2-p+2=0 | | M-1/2=(-5/4) | | 4x-1+113=180 | | 6(7x+5)=2130 | | 2x+25=12+15 | | 5x-50=5x+50 | | 3b+4b+7-3= | | 70+50+x+25=180 | | 9y+4=5(y-4) | | 5x+50=5x+50 | | 8(6x-5)=4760 | | y-4=1/2(x-15) | | -2.5+1.5y=11-3y | | Cos5x=1/2 | | u^2-11u-18=0 | | x(a+b)= | | -9-19=-14-14 | | 6(3/4)-1 | | -1(2)=2-4 | | 9(2x+5)=595 | | 8x+27-12y=7 | | 2x+48=2x-24 | | 0.75n-6=n+3 | | 34-5x+2(x-3)=2 | | (1/4-1/2);(3/4,2) | | x^3+y^3=91 | | xa^2+xb=c | | 5x+8=-167 | | 11-2x-6y=-11 | | 2x-3/5=3x+2 | | 6a+4b-a+9b= |